Development of Android-Based Mobile Learning Media on Market Balance Chapter Class X SMA Negeri 12 Surabaya - Aulya Sandy; Retno Mustika Dewi (Edumaspul: Jurnal Pendidikan, 2024)
This development research was carried out based on the lack of understanding of students and learning media in economics subjects. The aim of this research was to increase students' understanding through mobile learning media. This research uses the ADDIE model. The subjects of this research were students in class X7 of SMA Negeri 12 Surabaya. The design used is One Group Pretest Posttest. The research results showed that material expert validation obtained a percentage of 87%, including in the "Very Valid" category and media experts obtained a percentage of 86%, including in the "Very Valid" category. Media practicality obtained a percentage of 95.7% from students in the "Very Practical" category and 93% from teachers in the "Very Practical" category. The effectiveness of the media based on the completeness of learning outcomes obtained a percentage of 91.7% in the "Very Good" category. So the conclusion of this research is that mobile learning learning media is suitable and practical to use in learning because it is able to improve student learning outcomes. Keywords: Learning Media, ADDIE, Learning Outcomes.